Residual effect of vermicompost and thiourea on growth and yield attributes of mustard (Brassica juncea L) in semi arid regions of Agra - Chauhan, S.K.; Kumar, Parminder; Singh, S.K.; Goyal, V.; Singh, I.P. (Annals of Agricultural Research, 2014)
The field experiment was conducted during winter seasons (Rabi) of 2007-08 2008-09 in semiaridregions of Agra district to see the residual effect of vermicompost and thiourea on mustard crop(Brassica juncea L). The treatment included four levels of residual vermicompost and seven differentlevels of residual thiourea in a plot size of 4 x 3 m each with 3 replications. Mustard variety "PusaBold" was used. The growth characters of mustard i.e. plant height, no. of primary and secondarybranches /plant, no. of siliquae/plant, length of siliqua, no. of seeds/siliquae and test weightshowed a significant difference due to vermicompost residue left after the application in the precedingcrop up to a dose of 3.0 t/ha. However, with further increase in residual vermicompost level to 4.5t/ha, no significant difference in growth characters were observed. Similarly the seed and stoveryield also increased significantly with increase in residual vermicompost level up to a level of 3.0 t/ha. A significant difference was also observed in oil content and oil yield up to a residual level of 3.0t/ha and a maximum of 38.12 % and 743.22 kg/ha in oil content and yield was observed in treatmentplots with residual level of 3.0 t/ha. The residual effect of thiourea was found to be non-significantin all treatment levels.